Growth of Thalamocortical Fibers to the Somatosensory Cortex in the Human Fetal Brain - Krsnik, Željka; Majić, Visnja; Vasung, Lana; Huang, Hao; Kostović, Ivica (Frontiers in Neuroscience, 2017)
In the human brain the growth of thalamocortical (TH-C) fibers begins during embryonic period and is completed by the 3rd trimester of gestation. Here we have determined the timing and trajectories of the intrauterine growth of the somatosensory TH-C fibers in the human brain. The outgrowth, path-finding, „waiting“ in the subplate (SP), target selection and ingrowth in the cortical plate (CP) of the thalamocortical fibres were analyzed using histological sections from post-mortem fetal brain (from 7 to 34 postconceptional weeks-PCW) and processed by acetylcholinesterase (AChE) histochemistry and immunohistochemical methods. Images were compared with post mortem DTI-based fibre tractography (code No NO1-HD-4-3368). The results showed the outgrowth of the TH-C axons as early as 7.5 PCW in ventrolateral part of thalamic anlage. Between 8-9.5 PCW, TH-C axons form massive bundle and traverse diencephalic-telencephalic boundary. During the 9.5-11 PCW thalamocortical axons pass periventricular area at the pallial-subpallial boundary and enter intermediate zone in radiating fashion. Between 12-14 PCW, the TH-C axons, aligned along the fibers from the basal forebrain, continue to grow for a short distance within the deep intermediate zone and enter deep CP, parallel with expansion of the SP. Between 14-18 PCW, the TH-C interdigitate with callosal fibers, running shortly in sagittal stratum and spread through the deep subplate (“waiting” phase). From 19-22 PCW, TH-C axons accumulate in the superficial subplate, below somatosensory cortical area, two weeks earlier than in frontal and occipital cortex. Between 23-24 PCW, AChE reactive TH-C axons penetrate in CP concomitantly with its initial lamination. Between 25-34 PCW, AChE reactivity of the CP exhibits an uneven pattern suggestive of vertical banding showing, for the first time, basic 6-layer pattern. In conclusion, in human brain thalamocortical axons show prolonged growth (4 months), where somatosensory fibers precede ingrowth of fibers destined for the frontal and occipital areas. Major features of the growing TH-C somatosensory fiber trajectories are fan-like radiation, short run in sagittal strata and interdigitation with callosal system. These results support our previous suggestion that TH-C axons are early factors in morphogenesis and synaptogenesis of SP and CP and may regulate maturation of cortical somatosensory system.